Awareness of Orthopedic Surgeons and Neurosurgeons About Fragility Fractures and Fracture Liaison Services: A Survey Study - Fulya Bakılan; Gizem Sarıçimen; Burcu Ortanca; Onur Armağan (Galenos Yayinevi, 2024)
Objective: The aim of this study was to investigate the awareness of neurosurgeons and orthopedic surgeons working in Eskişehir about fragility fractures and fracture liaison services. Materials and Methods: A total of 50 surgeons (21 neurosurgeons, 29 orthopedic surgeons) responded to a survey about fragility fractures and fracture liaison services. Results: More than 95% of all the surgeons stated that they considered osteoporosis in patients who had a fracture with a low-level trauma. However, only 69% of the orthopedic surgeons and 61% of the neurosurgeons stated that they requested dual-energy X-ray absorptiometry in patients with fragility fractures. The rate of knowledge about the FRAX® algorithm was 17% in the orthopedic surgeons and 0% in the neurosurgeons. While 38% of the orthopedic surgeons stated that they performed both the treatment and follow-up of osteoporosis in patients with fragility fractures, 62% stated that they referred these patients. All the neurosurgeons stated that they did not perform osteoporosis treatment or follow-up and referred all their patients. Only one orthopedic surgeon was aware of fracture liaison services, while the other surgeons had no knowledge. Conclusion: The awareness of both the orthopedic surgeons and neurosurgeons about the management of fragility fractures and fracture liaison services was lower than expected.